2023
DOI: 10.1088/1402-4896/acf70a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into conduction band density of states at c-Si/TiO2 interface for efficient heterojunction solar cell

Sonal Santosh Bagade,
Piyush K Patel

Abstract: Carrier selective solar cell has become one of the hot spots in the area of Si solar cell. The proposed architecture FTO/TiO2/c-Si/i-a-Si:H/Cu2O/back contact studied through simulation demonstrates a power conversion efficiency of 20.03%. This study is the first to report detailed exploration of effect of the conduction band density of states on the efficiency of Si solar cell. Through optimization, the conduction band density of state (1017 cm-3) drastically increases the power conversion efficiency from 18% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 124 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…Optimization of band alignment is a very widely implemented designing technique in photovoltaic technology to enhance diffusion length [86][87][88][89][90]. This helps SC engineer to create hole-free space for electrons to flow towards electrode.…”
Section: Effect Of Band Alignment On Diffusion Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of band alignment is a very widely implemented designing technique in photovoltaic technology to enhance diffusion length [86][87][88][89][90]. This helps SC engineer to create hole-free space for electrons to flow towards electrode.…”
Section: Effect Of Band Alignment On Diffusion Lengthmentioning
confidence: 99%
“…Apart from the diffusion length enhancement, the another famously adopted method that gained prominence to increase the PCE of SC is the band-structure fine tuning to achieve the band offset optimization [89]. Takashi et al and Ding et al vividly demonstrated the effect of band offset optimization on SC performance parameters through their research work [86,88,90,93,137].…”
Section: Comparative Analysis On the Extent Of Effect Of Diffusion Le...mentioning
confidence: 99%